2016
DOI: 10.1002/ece3.2178
|View full text |Cite
|
Sign up to set email alerts
|

The effect of terrain and female density on survival of neonatal white‐tailed deer and mule deer fawns

Abstract: Juvenile survival is a highly variable life‐history trait that is critical to population growth. Antipredator tactics, including an animal's use of its physical and social environment, are critical to juvenile survival. Here, we tested the hypothesis that habitat and social characteristics influence coyote (Canis latrans) predation on white‐tailed deer (Odocoileus virginianus) and mule deer (O. hemionus) fawns in similar ways during the neonatal period. This would contrast to winter when the habitat and social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…This prompted efforts to estimate coyote population size and evaluate the potential for direct effects (i.e., predation) on Sonoran pronghorn (Bright and Hervert 2005). For ungulates in many systems, predation is a significant source of juvenile mortality (Linnell et al 1995), and coyotes have been implicated as the primary predators of neonatal white‐tailed deer ( Odocoileus virginianus ; Whittaker and Lindzey 1999, Lingle et al 2008, Kilgo et al 2012, Nelson et al 2015, Bonar et al 2016), mule deer ( Odocoileus hemionus ; Hamlin et al 1984, Whittaker and Lindzey 1999, Lingle et al 2008, Bonar et al 2016), and pronghorn ( Antilocapra americana ; Barrett 1984, Gese et al 1988 b , Berger et al 2008). In a 1995–2002 study, researchers reported 50% of predation‐caused Sonoran pronghorn mortalities ( n = 6) were attributable to coyotes (Bright and Hervert 2005).…”
Section: Figurementioning
confidence: 99%
“…This prompted efforts to estimate coyote population size and evaluate the potential for direct effects (i.e., predation) on Sonoran pronghorn (Bright and Hervert 2005). For ungulates in many systems, predation is a significant source of juvenile mortality (Linnell et al 1995), and coyotes have been implicated as the primary predators of neonatal white‐tailed deer ( Odocoileus virginianus ; Whittaker and Lindzey 1999, Lingle et al 2008, Kilgo et al 2012, Nelson et al 2015, Bonar et al 2016), mule deer ( Odocoileus hemionus ; Hamlin et al 1984, Whittaker and Lindzey 1999, Lingle et al 2008, Bonar et al 2016), and pronghorn ( Antilocapra americana ; Barrett 1984, Gese et al 1988 b , Berger et al 2008). In a 1995–2002 study, researchers reported 50% of predation‐caused Sonoran pronghorn mortalities ( n = 6) were attributable to coyotes (Bright and Hervert 2005).…”
Section: Figurementioning
confidence: 99%
“…Our landscape-scale results are consistent with mule deer exploiting terrain features as a predator avoidance mechanism by selecting steeper or more rugged slopes when stalking cover was lower (i.e., visibility was higher). Selection of areas with steeper slopes has been related to increased fawn survival for mule deer (Bonar et al, 2016). However, mule deer use of more rugged areas would be a better predator avoidance strategy for coursing rather than stalking predators (Bonar et al, 2016;Dellinger et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Selection of areas with steeper slopes has been related to increased fawn survival for mule deer (Bonar et al, 2016). However, mule deer use of more rugged areas would be a better predator avoidance strategy for coursing rather than stalking predators (Bonar et al, 2016;Dellinger et al, 2019). Mountain lions commonly select for areas with topographic complexity that also provide stalking cover (Robinson et al, 2015;Blake and Gese, 2016;Peterson et al, 2021), which may enhance kill success (Elbroch et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We then intersected each survey segment with the GPS locations for each white-tailed deer group detected. Segment-level spatial covariates included a bivariate smooth of geographic coordinates (Universal Transverse Mercator [UTM]) to account for spatially autocorrelated whited-tailed deer detections and land cover types known to influence deer abundance such as distance from agriculture cover (m) [40][41][42][43], distance from developed cover (m) [42][43][44][45], distance from forest cover (m) [42,46,47], distance from shrub cover (m) [43,48,49], distance from timber cuts (m) [48,50], distance from wetland cover (m) [43,51,52], distance from water (m) [51,53], elevation (m) [12,54,55], and days with snow cover [56,57]. Land cover such as agriculture, developed, forest, shrub, timber cuts, wetland, and water were identified using an updated land cover map of the Park for 2016 that combined Landsat 8 satellite imagery (30 m resolution) acquired from the USGS Global Visualization Viewer for imagery, Normalized Difference Vegetation Index, National Land Cover Dataset, the Adirondack Park Agency's wetlands data, and timber treatment data provided by regional timber companies [24].…”
Section: Discussionmentioning
confidence: 99%